2015
DOI: 10.1016/j.fsi.2015.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Multiple biomarkers of biological effects induced by cadmium in clam Ruditapes philippinarum

Abstract: a b s t r a c tCadmium (Cd) is a known heavy metal pollutant in the Bohai Sea. Manila clam Ruditapes philippinarum is an important fishery species along the Bohai coast. In this study, the biological effects induced by two concentrations (20 and 200 mg/L) of Cd were characterized using multiple biochemical indices in the digestive glands of clam R. philippinarum. The total hemocyte counts, reactive oxygen species productions and antioxidant enzyme activities exhibited that Cd induced dose-dependent immune and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Interestingly, decreased succinate and alanine and increased aspartate were found in Cd-treated Dshape larval mussels, which suggested that Cd exposure reduced the anaerobiosis in D-shape larval mussels. In clam Ruditapes philippinarum, however, the anaerobiosis was enhanced by Cd exposure (Ji et al 2015). The contrary findings meant the species-specific effects in anaerobiosis induced by Cd in marine bivalves.…”
Section: Resultsmentioning
confidence: 87%
“…Interestingly, decreased succinate and alanine and increased aspartate were found in Cd-treated Dshape larval mussels, which suggested that Cd exposure reduced the anaerobiosis in D-shape larval mussels. In clam Ruditapes philippinarum, however, the anaerobiosis was enhanced by Cd exposure (Ji et al 2015). The contrary findings meant the species-specific effects in anaerobiosis induced by Cd in marine bivalves.…”
Section: Resultsmentioning
confidence: 87%
“…It may induce oxidative stress in organisms by producing excessive reactive oxygen species [3]. Additionally, Cd can disturb the energy metabolism in clam Ruditapes philippinarum indicated by the enhanced anaerobic metabolism [4]. Since Cd has become one of the most severe metal contaminants in the Bohai Sea, it is necessary to characterize the biological effects of Cd in marine animals.…”
Section: Introductionmentioning
confidence: 99%
“…KEGG annotation showed that betaine was related to ABC transporters and the glycine, serine, and threonine metabolism. Ji et al (2015) used betaine as a biomarker of Cd stress in clams.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics has been widely used in the study of plants ( Sumner et al, 2003 ; Mwamba et al, 2020 ), animals ( Ji et al, 2015 ; Kim et al, 2016 ; Song et al, 2018 ), microorganisms ( Milreu et al, 2013 ), and ecosystems ( Boroujerdi et al, 2009 ), as well as in elucidating the toxicity mechanisms of pollutants because it maps alterations in metabolites induced by exposure ( Nicholson et al, 1999 ; Sugiura et al, 2005 ). The high applicability of metabolomics is because it qualitatively and quantitatively characterizes the chemical characteristics of low-molecular metabolites (<1,000 Da), which are the final products of cell regulatory pathways in cells, tissues ( Cappello, 2020 ; Sun et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%